Dynamics of Employee Retirement Protection through Severance Pay Mechanisms - Noferman Gea (Program Pascasarjana STIE Amkop Makassar, 2026)
Severance pay has gacorwin become an important mechanism in protecting employees from the economic risks associated with termination of employment. This study aims to examine the role of severance pay as a retirement protection mechanism and analyze the factors that influence its effectiveness. This study uses a qualitative descriptive gacorwin approach using secondary data obtained from academic journals, policy reports, and organizational documents. The findings indicate that severance pay serves not only as financial gacorwin compensation but also as an economic protection instrument that supports employee financial well-being, family economic stability, and retirement security. Severance pay policies influence perceptions of job security, employee motivation and loyalty, and perceptions of organizational fairness.